Isocyanoalkenes: Occurrence, Syntheses, and Reactivity - Tian, Huan; Fleming, Fraser F. (Synthesis, 2025)
Isocyanoalkenes are a largely underexplored subset of isocyanides whose natural occurrence, synthesis, and reactivity are elucidated in this review. The discussion begins with an overview of the biosynthesis and natural occurrence, which provides a valuable context for the synthetic approaches to these unusual π-substituted alkenes. Building on this foundation, the review explores the characteristic reactivity of isocyanoalkenes, which is shaped by the strong electron-withdrawing nature of the isocyanide group and an almost complete lack of π-conjugation. Two primary modes of reactivity are highlighted: conjugate additions – especially in systems containing additional electron-withdrawing substituents – and radical additions to the isocyanide, often followed by annulation via iminyl radical intermediates. Special attention is given to two particularly versatile isocyanoalkenes – β-dimethylaminoisocyanoacetates and β-bromoisocyanoacetates – which readily undergo nucleophilic addition–elimination–cyclization sequences to efficiently assemble nitrogen-containing heterocycles. Overall, this review underscores the synthetic potential of isocyanoalkenes and highlights their emerging value in the construction of diverse heterocyclic scaffolds.
Keywords: Isocyanoalkenes; Synthesis; Reactivity; Additions; Heterocycles